"Not Only for a Celebration of Competitive Overwatch but Also for National Pride": Sportificating the Overwatch World Cup 2016. Issue 4 (June 2020) - Turtiainen, Riikka; Friman, Usva; Ruotsalainen, Maria
While the most popular forms of organized competitive digital gaming, also known as eSports, have begun finding their place within and in relation to both mainstream entertainment culture and the field of traditional sports, their history is one of struggling to be accepted as "true sports." Partly because of this history, great effort has been put into the sportification of eSports by presenting competitions in familiar ways adapted from traditional sports. In this article, we examine the process of sportification of eSports in the context of tournament broadcasts. We analyze the Overwatch World Cup 2016 tournament, comparing its final broadcast to the 2014 FIFA World Cup's final broadcast, looking for similarities and differences in the areas of broadcast structure, commentary and expertise, game presentation, game highlights and acknowledgments, teams and players, and audience.